الأداء الوظيفي والجمالي لبعض أعمال التريكو اليدوي منتجة من عوادم أقمشة التريكو - خضير، إيمان بهنسي أحمد (جامعة دمياط - كلية الفنون التطبيقية, 2015)
يعتبر التلوث من الظواهر البيئية التي تأخذ قدرا كبيرا من الاهتمام على المستوى الدولي وهي مشكلة ملحة تأخذ أبعاد بيئية واقتصادية خطيرة والملابس تمثل موارد ذات فائدة اقتصادية حيث يهدف هذا البحث إلى إمكانية الاستفادة من عوادم مصانع الملابس والنسيج وإعادة تدويرها كنوع من المشاركة في الحد من التلوث البيئي الناتج عن هذه المخلفات وذلك من خلال أعمال التريكو اليدوي المنتجة من عوادم أقمشة التريكو. ولتحقيق هذا الهدف تم تجميع العديد من عوادم القص لقماش التريكو المتنوعة من مصانع الملابس الجاهزة وتم تحديد أشكال القطع والتي سيتم تنفيذها (طاقية والكوفية وشراب القدم) وتم استخدام الغرزة المقلوبة وغرزة الجرسية وغرزة البليسية 1/1. تم إعداد استبانة لقياس الجانب الوظيفي والجانب الجمالي بهدف إجراء تحكيم للقطع المنفذة وتم تحليل آراء المحكمين إحصائيا بواسطة برنامج (SPSS) لإيجاد التوزيع التكراري والمتوسط الحسابي والانحراف المعياري وحساب الفروق المعنوية. وأظهرت النتائج أن الموديل الخامس والأول بالتوالي سجل أعلى قيمة مقارنة بباقي النماذج حيث سجلت النتائج الخاصة بالجانب الجمالي ومستوى الأداء الوظيفي وبإجراء اختبار التباين تبين أنه يوجد فروق ذات دلالة معنوية بين الموديلات المنفذة. أيضا وجود علاقة طردية موجبة بين المحور الأول وعناصره كما تبين بوجود نفس العلاقة وعند نفس المستوي للمحور الثاني وعناصره. لذا يوصي البحث إقامة ندوات ومؤتمرات للتوعية بأهمية الحفاظ على البيئة من التلوث يتم توجيهها إلى أصحاب مصانع الملابس الجاهزة وطلاب الكليات المتخصصة مع ضرورة التعاون بين أصحاب المصانع والكليات المتخصصة لاستغلال مخلفات تلك المصانع بصورة تحافظ على البيئة من التلوث.
The pollution of environmental phenomena that take a great deal of attention at the international level, a pressing problem take a serious environmental and economic dimensions and clothing represent the same economic benefit resources. The research aims to take advantage of exhaust clothing and textile factories and recycled as a form of participation in the reduction of output for this waste and environmental pollution through hand-knitted from producer exhaust knitted fabrics business. To achieve this goal, several of exhaust shear compilation of various knitted fabric of the garment factories were identified forms of the pieces which will be implemented (hat and scarf and drink foot) was used inverted stitch, knit stitch, purl stitch. and prepared questionnaire to measure the functional aspect and aesthetic value to conduct arbitration cutting executed were analyzed the views of the arbitrators statistically "by software (SPSS) to find a frequency distribution and the arithmetic mean, standard deviation, and the expense of moral differences. The results showed that the Model No. 5 and 6, respectively the highest value recorded compared to other models where Results own side of the aesthetic and the level of job performance recorded and test variability was found that there were significant differences between the models implemented differences. Also having a positive direct correlation between the first axis and elements also show the presence of the same relationship and at the same level for the second axis and its components. So research recommends the establishment of seminars and conferences to raise awareness the importance of preserving the environment from pollution is routed to the owners of garment factories and students of specialized colleges with the need for cooperation between the factories and specialized colleges owners to exploit the remnants of these plants are maintained on the environment from pollution.
Keywords: أقمشة التريكو -- القيم الجمالية -- التراكيب النسيجة -- التريكو اليدوي